AB0173 Overwhelming inflammation increased susceptibility of sle-prone mice to pulmonary bactreial infection. (12th June 2018) - Li, W.; Tang, X.; Huang, S.; Sun, L.
Abstract : Background: Aside from the disease itself, infections represent the major cause of morbidity and mortality in systemic lupus erythematosus (SLE) patients. Inherent defects in immune system play an important role in increasing rates of infection. However, the underlying mechanism of this dificiency remains largely unknown. Methods: Lupus-prone mice B6/ lpr were anaesthetized and infected with 1×10^8 CFU of Haemophilus influenzae (Hi) intranasally. Then bacterial clearance, body weight change and lung pathology were monitored. Apoptosis of lung cells was analysed by TUNEL assay. Both innate and adaptive immune response in the lung cells determined by flow cytometry. Cytokines in the bronchoalveolar lavage fluid (BALF) were measured by ELISA. Results: Although both wild-type (WT) and B6/ lpr mice survived after pulmonary Hi infection, a delay of bacterial clearance and inflammatory resolution was observed in B6/ lpr mice. Tissue damage was more severe in the lungs of B6/ lpr mice, as more apoptotic cells were detected on Day2 after infection. Cells from lupus-prone lungs produced more pro-inflammatory cytokines IL-6, MCP-1 and KC. TNF-α is comparable between the two groups. NK, γδ T and CD4 T cells are required for control bacterial infection. We that compared with WT controls, in response to infection fewer NK cells were detected in B6/ lpr lungs. The numbers of γδ and CD4 T cells were not different, but their ability to secrete IFN-γ was significant lower in B6/ lpr mice. Conclusions: The increased susceptibility of SLE-prone mice to pulmonary Haemophilus influenzae infection may due to the elevated inflammatory responses and the deficient production of IFN-γ by immune cells. Disclosure of Interest: None declared